Pengaruh Kemampuan Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Kai Logistik - Ade Akhmad Rizki (JURNAL RISET MANAJEMEN (JURMA), 2023)
Human resources are potential or assets that are material capital. Ini organizations and problem that can be realized into real potential physically and non-physically.The scope of this research is the Effect of Ability and Work Motivation on Employee Performance at PT KAI Logistik. The purpose of this study is to determine the effect of Ability and Work Motivation on Employee Performance at PT KAI Logistik. the method used is multiple linear regression using questionnaire data distributed to 35 respondents at PT KAI Logistik.The results showed that ability has a partial effect on employee performance with t_count (15.261) > (1.69389) t_(table ) while the sig value (0.00) < (0.050) work motivation variable has a partial effect on employee performance with a t_count value (7.901) > (1.6389) t_(table) and when viewed from the sig value (0.00) < (0.05) Work Ability and Motivation affect employee performance simultaneously with an f_count value of (154.831) > (3.29). Work ability and motivation have a partial and simultaneous effect on employee performance at PT KAI Logistik.